P-122 Restarting our day services post COVID – The Living Well Programme. (19th November 2022) - Stone, Helen; Drake, Karen
Abstract : During COVID we were able to keep our day service running outside of the hospice via volunteer telephone support and remote activity packs which were well received. We were given permission to re-open our service for face-to-face support in March 2022, two years after we had closed. Having taken the time to review how we wanted to take our service forward we decided to start with our new Living Well Programme. This was to be a 12 week programme of education for patients to empower and enable them to take control of their illness and live the best quality of life possible. Sessions include symptom management (pain, constipation, breathlessness, fatigue); well-being (complementary therapy, anxiety, exercise); practical advice (falls prevention, medication management); as well as advance care planning and an overview of hospice services. We were able to take five patients into the first programme. There were several challenges to commencing the service; having been closed to referrals for 2 years this process was slow to start and a lot of promotion of the new programme was needed for the CNS team. The challenge in receiving referrals was also impacted by the continued high pressure of workload and staffing pressures. The start date was then further impacted by continued pressures on our service, staffing, recruitment and patient unavailability. The first sessions started in April 2022, three out of five booked attended. It was a very successful day with people learning about the support the hospice can give and enjoying each other's company. Feedback was 'enjoying meeting others ' and 'meeting others with cancer for the first time since diagnosis '. The first Living Well Programme was a success with feedback around the companionship and support from people in similar situations, and the helpfulness of the topics both for now and the future. Overall the first programme benefitted 7 patients. The programme has now started its second run and will be a rolling programme moving forward.